2015
DOI: 10.13065/jksdh.2015.15.03.411
|View full text |Cite
|
Sign up to set email alerts
|

Oral health status and care needs of elderly patients in long-term care hospital

Abstract: Objectives: The purpose of this study is to identify oral health status and oral health care needs of elderly patients in long-term care hospital. Methods: Oral health examination was carried out by a dentist and questionnaire was completed by direct individual interview by a dental hygienist for 245 elderly patients in seven long-term care hospitals in Daegu from March 12 to April 16, 2011. Results: Those who need dental care were 188(76.7%) and was done by oral health examination by a dentist. 93 patients(38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Due to a lack of knowledge and skills, caregivers do not understand the harmful consequences of poor oral hygiene to the health of elderly individuals [22]. Thus, in addition to adequate training, a continuing education program in oral health for caregivers is very important to meeting the specific demands of the geriatric public [13,14,22,23]. Challenges regarding the oral hygiene rou-tine are related to the health conditions of the elderly, the caregivers themselves and the underlying socio-cultural context.…”
Section: Discussionmentioning
confidence: 99%
“…Due to a lack of knowledge and skills, caregivers do not understand the harmful consequences of poor oral hygiene to the health of elderly individuals [22]. Thus, in addition to adequate training, a continuing education program in oral health for caregivers is very important to meeting the specific demands of the geriatric public [13,14,22,23]. Challenges regarding the oral hygiene rou-tine are related to the health conditions of the elderly, the caregivers themselves and the underlying socio-cultural context.…”
Section: Discussionmentioning
confidence: 99%
“…This increase in the number of inpatients suggests a need for comprehensive oral health management, including general health. Oral health and general health are closely related, so during long-term inpatient treatment, it is difficult to maintain oral health 5,6) . Go et al 7) reported that professional oral care and education are essential for long-term care hospital inpatients who have difficulty in self-care.…”
Section: Introductionmentioning
confidence: 99%